Strategic Environmental Assessment (SEA) of Rural Development Programs in the European Union – Towards a More Efficient Monitoring of the Environmental Effects of Agricultural Policies - Spaziante, Agata; Rega, Carlo; Carbone, Mirko; Murano, Chiara (IntechOpen, 2012)
None